Genetic diversification of an invasive honey bee ectoparasite across sympatric and allopatric host populations - Beaurepaire, Alexis (2022)
Invasive parasites are major threats to biodiversity. The honey bee ectoparasite, Varroa destructor, has shifted host and spread almost globally several decades ago. This pest is generally considered to be the main global threat to Western honey bees, Apis mellifera, although the damages it causes are not equivalent in all its new host's populations. Due to the high virulence of this parasite and the viruses it vectors, beekeepers generally rely on acaricide treatments to keep their colonies alive. However, some populations of A. mellifera can survive without anthropogenic mite control, through the expression of diverse resistance and tolerance traits. Such surviving colonies are currently found throughout the globe, with the biggest populations being found in Sub-Saharan Africa and Latin America. Recently, genetic differences between mite populations infesting surviving and treated A. mellifera colonies in Europe were found, suggesting that adaptations of honey bees drive mite evolution. Yet, the prevalence of such co-evolutionary adaptations in other invasive populations of V. destructor remain unknown. Using the previous data from Europe and novel genetic data from V. destructor populations in South America and Africa, we here investigated whether mites display signs of adaptations to different host populations of diverse origins and undergoing differing management. Our results show that, contrary to the differences previously documented in Europe, mites infesting treated and untreated honey bee populations in Africa and South America are genetically similar. However, strong levels of genetic differentiation were found when comparing mites across continents, suggesting ongoing allopatric speciation despite a recent spread from genetically homogenous lineages. This study provides novel insights into the co-evolution of V. destructor and A. mellifera, and confirms that these species are ideal to investigate coevolution in newly established host-parasite systems.